The most suitable types of obturator for stomatognathic system rehabilitation after maxillofacial surgery: A systematic review - Riezky Rhamdani; Irfan Dammar (Journal of Dentomaxillofacial Science, 2022)
Objective: To find out the best type of obturator in the rehabilitation of stomatognathic system in patients after maxillofacial surgery. Methods: Using MeSH (Medical Subject Headings) terms, an online search were conducted in PubMed database with keywords “maxillofacial surgery” and “obturator”. The search was limited to the articles that publish between 2013 to 2017. There are 74 journals found in initial search, but only 3 journals meet the inclusion criteria. Results: The database search yielded 74 references from PubMed. The titles and abstract were reviewed afterward, and 22 studies were eligible for further analysis. The full-texts been reviewed by the reviewer and yielded 3 articles which meet the inclusion criteria, with the total patients were 76 people. In those studies, they were using conventional obturator, cast partial obturator, hollow bulb obturator, magnet obturator, stud attachment retained obturator and implant supported obturator. Obturator Function Scale (OFS) was used in this review as guideline to compare those studies’ result. Conclusion: Stud Attachment retained obturator has the best OFS rating in terms of aesthetics, nasal leakage, speech enhancement, and chewing / eating.